Single Dose Methotrexate in Successful Evacuation of Second Trimester Placenta Accreta - Snehal Deshmukh Senior1 , Mugdha Jungari2 , Priya Nair3 , Kshipra Bhangdia4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Morbidly adherent placenta is a serious and life-threatening condition. High index of suspicion for placentaaccreta can save patient from undergoing hysterectomy. Timely and appropriate treatment modality is keyin reducing morbidity of the patient Reporting herewith a case of 22-24 weeks intrauterine fetal demisein a primigravida patient who was diagnosed with Placenta accreta. Ultrasonography and MRI confirmedthe diagnosis. Primigravida with no live issue, no active bleeding and stable vital parameters favoredthe option of conservative management in the form of “single dose methotrexate regime”. Patient wasthen given Injection methotrexate 50 mg IM on day 1. Regularly monitored with CBC(complete bloodcount),LFT(Liver Function Test),KFT(kidney Function Test), beta HCG, USG and pelvic doppler. On day 7piecemeal removal of complete placenta accrete was successful under USG guidance.